Initial testing of a pixelated silicon detector prototype in proton therapy - Wroe, Andrew J.; McAuley, Grant; Teran, Anthony V.; Wong, Jeannie Hsiu Ding; Petasecca, Marco; Lerch, Michael; Slater, James M.; Rozenfeld, Anatoly B. (Wiley Open Access, 2017)
As technology continues to develop, external beam radiation therapy is being employed, with increased conformity, to treat smaller targets. As this occurs, the dosimetry methods and tools employed to quantify these fields for treatment also have to evolve to provide increased spatial resolution. The team at the University of Wollongong has developed a pixelated silicon detector prototype known as the dose magnifying glass (DMG) for real-time small-field metrology. This device has been tested in photon fields and IMRT. The purpose of this work was to conduct the initial performance tests with proton radiation, using beam energies and modulations typically associated with proton radiosurgery. Depth dose and lateral beam profiles were measured and compared with those collected using a PTW parallel-plate ionization chamber, a PTW proton-specific dosimetry diode, EBT3 Gafchromic film, and Monte Carlo simulations. Measurements of the depth dose profile yielded good agreement when compared with Monte Carlo, diode and ionization chamber. Bragg peak location was measured accurately by the DMG by scanning along the depth dose profile, and the relative response of the DMG at the center of modulation was within 2.5% of that for the PTW dosimetry diode for all energy and modulation combinations tested. Real-time beam profile measurements of a 5 mm 127 MeV proton beam also yielded FWHM and FW90 within ±1 channel (0.1 mm) of the Monte Carlo and EBT3 film data across all depths tested. The DMG tested here proved to be a useful device at measuring depth dose profiles in proton therapy with a stable response across the entire proton spread-out Bragg peak. In addition, the linear array of small sensitive volumes allowed for accurate point and high spatial resolution one-dimensional profile measurements of small radiation fields in real time to be completed with minimal impact from partial volume averaging.